CONFOCAL STUDIES OF ARBUSCULAR MYCORRHIZAL FUNGI COLONIZING THE SPOROPHYTE OF BOTRYCHIUM DAUCIFOLIUM Wall., A RARE FERN OF INDIA: Life Sciences-Plant Science - R, SARALA; S.R., SENTHILKUMAR (International Journal of Life Science and Pharma Research, 2012)
The arbuscular mycorrhizal (AM) fungi colonizing the sporophyte of the rare fern, Botrychium daucifolium, Ophioglossaceae were investigated in the present study. The roots of the sporophyte were analyzed for the presence of AM fungi. The confocal analysis of mycorrhizal association revealed the different stages of fungal lysis and degradation which served as the nutrients for the host cells. The AM fungi associated with the fern was identified to be Glomus species.